OPTIMIZATION OF SHIFT SCHEDULING OF EMPLOYEES OF K3 MART INDEPENDENT FIELD BRANCH IN MEDAN USING INTEGER LINEAR PROGRAMMING - Afriani, Widya (Pena Cendekia Insani, 2023)
Effective shift scheduling is an important element in human resource management at K3 Mart, Lapangan Merdeka, Medan, which operates for 24 hours. Challenges such as uneven shift distribution, disproportionate work schedules, and errors due to manual scheduling can reduce productivity, increase employee fatigue, and trigger internal conflicts. This research aims to optimize shift scheduling using the Integer Linear Programming (ILP) method. Primary data from employee interviews is used to build a mathematical model. The model is designed to minimize the number of workers in one scheduling period, while still considering constraints such as minimum employee requirements per shift, fair shift rotation, and a balanced distribution of days off. Model processing is done using Dev-C++ software, resulting in an optimal schedule that can meet operational needs without causing conflicts or labor shortages. The results show that the ILP method is able to produce an efficient, fair, and productivity-enhancing schedule, while maintaining workload balance and employee health. In addition, this method is flexible to adjust to changing operational needs. Implementation of this method in the retail sector can improve operational efficiency and employee welfare, with regular evaluation and updates to ensure its sustainability.